Neonatal myocardial infarction and the role of extracorporeal membrane oxygenation. Issue 1 (15th June 2007) - Ferns, S; Khan, M; Firmin, R; Peek, G; Bu'Lock, F
Abstract : Acute myocardial infarction is a cause of neonatal collapse. The diagnosis is suggested by ischaemic electrocardiography, raised cardiac enzymes and deteriorating cardiac function and should be considered in severe neonatal cardiac dysfunction without other identifiable causes. This paper presents four cases of neonatal myocardial infarction treated with veno-arterial extracorporeal membrane oxygenation (VA ECMO) for cardiorespiratory support. The paper illustrates that left ventricular function may recover after neonatal myocardial infarction if it can be supported for long enough, and that early ECMO referral may be of benefit.